Πειραματική μελέτη ροής παθητικού μικροαναμικτή τύπου λαβύρινθου με χρήση τεχνικής micro-PIV - Γιαννόπουλος, Αντώνιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Ρευστών. Εργαστήριο Αεροδυναμικής, 2016)
The present diploma thesis examines experimentally the flow of water in a passive, planar, split and merge micromixer with labyrinth-type channels ,of depth 60 μm, via the micro-PIV technique, for Re number 0.5 . In particular, the velocity field in 3 depths is examined, as well as the concentration field via an image processing code in order to study the diffusion and convection(Dean Vortices) phenomena. Although the Re number was quite low, a slightly 3D flow pattern was revealed, as well as some mass convection phenomena in the junction areas which contribute greatly to mixing.